Pengaruh Personal Branding Jovi Adhiguna Di Instagram Terhadap Minat Fashion Androgini (Survey Pada Followers Akun Instagram @ joviadhiguna) - Bertha K. Sinambela; Saskia Novendra (Communication Science Department - Faculty of Social and Political Sciences, Universitas Satya Negara Indonesia (USNI), 2023)
Abstract - Androgynous fashion in Indonesia is becoming known to the public through several androgynous influencers or content creators. They managed to express themselves as androgynous figures on social media, one of which was Instagram. Every influencer has the influence to encourage people, especially their followers to try to follow their lifestyle, or imitate their dress style. The theory used in this study is the theory of Computer Mediated Communication or CMC where the theory is a communication process using computer technology media. This research uses a positivistic paradigm, a quantitative approach, survey methods, and the nature of explanatory research. The total population is 809,000 followers from the @joviadhiguna instagram account and taking samples using the slovin formula with a large 10% error rate, so as to get 100 samples. Data analysis used correlation test, simple linear regression, determination test, and t test. The result of the research is the correlation value is 0.626 (6.26%) then the t_count value is 7.948 above the t_table value of 1.985 with a significance value of 0.00.